Unconscious dominions : psychoanalysis, colonial trauma, and global sovereignties. - Anderson, Warwick; Jenson, Deborah; Keller, Richard C. (Duke University Press, 2011)
By the 1920s, psychoanalysis was a technology of both the late-colonial state and anti-imperialism. Insights from psychoanalysis shaped European and North American ideas about the colonial world and the character and potential of native cultures. Psychoanalytic discourse, from Freud’s description of female sexuality as a “dark continent” to his conceptualization of primitive societies and the origins of civilization, became inextricable from the ideologies underlying European expansionism. But as it was adapted in the colonies and then the postcolonies, psychoanalysis proved surprisingly useful for theorizing anticolonialism and postcolonial trauma.